Insulating coating slurry and application thereof
By adding thixotropic agent to the insulating coating slurry of lithium-ion batteries to form a three-dimensional mesh structure, the problem of traditional coatings being mutually dissolved during high-speed coating is solved, and the rapid improvement of slurry viscosity and battery performance are achieved.
Patent Information
- Application Number
- CN202411994518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
AI Technical Summary
During the preparation of lithium-ion batteries, the traditional insulating coating and the positive electrode active material coating area have severe mutual solubility during the high-speed coating process, resulting in excessive width of the mutually soluble coating area and blurred boundaries, affecting the energy density and safety performance of the battery.
An insulating coating slurry is used, which includes insulating filler, binder and thixotropic agent. By forming a three-dimensional mesh structure in the slurry system, the thixotropy of the slurry is enhanced, so that its viscosity is reduced when it is inside the coating equipment, and it is convenient for transportation; after leaving the coating die head, the viscosity increases rapidly, reducing the mutual dissolution with the active material coating.
It effectively reduces the mutual dissolution and interpenetration of the insulating coating and the active material coating, reduces the width of the mutual dissolution coating area, improves the energy density and safety performance of the battery, and avoids the problem of excessive pressure in the coating equipment.
Smart Images

Figure CN119842249A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to an insulating coating slurry and its application. Background Art
[0002] With the rapid development of society, energy shortage has become an urgent problem to be solved. In order to solve the energy problem, my country actively promotes the development of new energy. In the field of new energy, whether it is the storage of renewable energy or the power demand of new energy vehicles, lithium-ion batteries are indispensable.
[0003] In the preparation process of lithium-ion batteries, in order to reduce the edge burrs generated during the cutting process of the pole piece and prevent the burrs from penetrating the diaphragm and causing a short circuit in the battery, which may cause safety hazards, battery manufacturers usually apply an insulating coating with PVDF as a binder and ceramics such as boehmite / alumina as fillers on the edge of the lithium battery pole piece. During the high-speed coating process (shear rate of about 50 / s), the traditional edge coating with PVDF as a binder and the positive electrode active material coating area have serious mutual dissolution phenomenon, resulting in excessive width of the mutual dissolution coating area and blurred boundaries. On the one hand, this phenomenon will reduce the recognition accuracy of the CCD (charge coupled device) in the back-end process and cause cutting deviation. If it is biased towards the positive electrode active material coating area, the edge of the pole piece will not be protected by the edge coating, resulting in waste of the main material; if it is biased towards the insulating coating area, the width of the insulating coating area will be too large and the energy density of the battery cell will be reduced; on the other hand, the more serious the mutual dissolution phenomenon, the more positive electrode active materials will enter the mutual dissolution coating, which will reduce the positive electrode active materials in the active material coating, and ultimately reduce the battery capacity; the subsequent battery energy performance will also increase the impedance at the boundary, resulting in uneven charging / discharging and reduced capacity. In addition, if only the slurry viscosity is increased, the problem of mutual penetration can be improved to a certain extent, but it will cause excessive pressure on the coating equipment and cannot meet the actual production needs. Summary of the invention
[0004] The main purpose of the present application is to provide an insulating coating slurry for solving the problem of mutual dissolution and interpenetration of the slurries in the active material coating area and the insulating coating area on the electrode plate collector at a higher coating rate.
[0005] In order to achieve the above objectives, this application provides the following technical solutions.
[0006] A first aspect of the present application provides an insulating coating slurry, which includes an insulating filler, a binder and a thixotropic agent; the mass ratio of the insulating filler to the binder is (90:10)-(60:40), for example, it can be 90:10, 85:15, 80:20, 78:22, 75:25, 70:30, 65:35, 60:40, etc.; the mass of the thixotropic agent is 0.1%-20% of the sum of the mass of the insulating filler and the binder, for example, it can be 0.1%, 0.5%, 1%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, etc.
[0007] Preferably, the mass ratio of the insulating filler to the binder is (85:15)-(70:30); preferably, the mass of the thixotropic agent is 1%-10% of the sum of the mass of the insulating filler and the binder.
[0008] A thixotropic agent is added to the insulating coating slurry of the present application and is used in combination with an insulating filler and a binder. The thixotropic agent can form a three-dimensional network structure in the insulating coating slurry system, thereby improving the thixotropy of the slurry and increasing the thixotropic index of the slurry. That is, when the insulating coating slurry is inside the coating equipment, it is subjected to high shearing action, the three-dimensional network structure is destroyed, and the viscosity of the slurry is reduced, making it easier to transport and convey; when the slurry leaves the coating die head and is coated on the current collector, the shearing action rapidly decreases or even disappears, and the three-dimensional network structure rapidly recovers, causing the viscosity of the slurry to rapidly increase. Under a higher viscosity state, the insulating coating slurry is not easy to diffuse, which can effectively reduce the mutual dissolution and interpenetration of the insulating coating slurry and the active slurry.
[0009] The ratio of each component in this application will affect the performance of the insulating coating slurry. Specifically, the ratio of insulating filler to binder affects the baseline viscosity of the slurry (within the said ratio range, the more binder content, the higher the slurry viscosity), laser cutting after drying (too much binder will not be cut, too little will cause powdering), coating peel strength (the more binder content, the higher the peel strength) and whether the subsequent coating will powder (too little binder content will cause powdering). When the mass of the thixotropic agent is too small to the sum of the mass of the insulating filler and the binder, the three-dimensional network structure formed in the insulating coating slurry system is imperfect, and the improvement of the thixotropy of the slurry is small; if the proportion is too large, the slurry will be too thixotropic and the slurry viscosity will be too large under low shear, which will affect the normal flow of the slurry before entering the coating equipment and cannot meet the use requirements.
[0010] Furthermore, the insulating coating slurry has a viscosity (η 50 / s ) is 1000-10000 mPa·s; for example, it can be 1000, 2000, 2500, 3000, 5000, 7000, 8500, 9500, 10000 mPa·s, etc. More preferably, it is 1500-4000 mPa·s.
[0011] At room temperature, the shear rate of 50 / s is the approximate shear rate to which the insulating coating slurry is subjected when it is extruded from the coating die head at a higher coating rate. This parameter can reflect the viscosity state of the slurry in the actual production process. Under this viscosity state, the thixotropy of the insulating coating slurry is more conducive to play a role. If η 50 / s Too high viscosity will make the slurry difficult to transport or convey. 50 / s If the viscosity is too low, the thixotropy of the slurry will be affected, which is not conducive to reducing the mutual solubility and interpenetration of the insulating coating slurry and the active slurry.
[0012] Furthermore, the thixotropic index of the insulating coating slurry is 15≤TI≤50, for example, it can be 15, 20, 28, 35, 40, 45, 50, etc. The thixotropic index reflects the recovery speed of the slurry viscosity, and within a specific range, the larger the thixotropic index, the faster the recovery speed of the slurry viscosity, and the more it can suppress the mutual dissolution and interpenetration of the insulating coating slurry and the active slurry at a higher coating rate. Further preferably, the thixotropic index of the insulating coating slurry is 20≤TI≤40.
[0013] The thixotropic index is the viscosity (η) of the insulating coating slurry at a shear rate of 1 / s at room temperature. 1 / s ) and the viscosity of the insulating coating slurry at a shear rate of 50 / s at room temperature (η 50 / s ) ratio.
[0014] Furthermore, the insulating filler includes at least one of aluminum oxide, boehmite, magnesium oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium silicon oxide, barium zirconate, aluminum nitride, silicon nitride, and barium titanate.
[0015] Furthermore, the polymer binder comprises at least one of polyvinylidene fluoride and its modified products, polyacrylic acid polymers, polyvinyl acetate polymers, polyacrylonitrile polymers, polyacrylate polymers, polyurethane polymers, polyurea polymers, and polyimide polymers;
[0016] Preferably, the polymer binder comprises at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyvinyl acetate (PVAC), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyimide (PI);
[0017] Furthermore, the thixotropic agent includes an inorganic thixotropic agent and / or an organic thixotropic agent.
[0018] The inorganic thixotropic agent includes at least one of fumed silica, precipitated silica, organic bentonite, metal soap, asbestos, kaolin and attapulgite.
[0019] Preferably, the specific surface area of the fumed silica and / or precipitated silica is 50-500 m 2 / g, for example, 50, 80, 100, 130, 170, 200, 280, 300, 350, 400, 450, 500 m 2 / g, which is conducive to forming a three-dimensional network structure in the slurry system; more preferably 100-280m 2 / g; more preferably 130-170m 2 / g.
[0020] The organic thixotropic agent includes at least one of polyurea, polyethylene wax, polyamide wax, polyisoprene, hydroxyethyl cellulose, hydrogenated castor oil and polyvinyl chloride. The polyvinyl chloride is preferably prepared by an emulsion method.
[0021] The preparation method of the above-mentioned insulating coating slurry comprises the following steps: 1) dispersing an insulating filler in a solvent (which may be N-methylpyrrolidone, without particular limitation) to obtain a solution A; 2) dispersing a polymer binder in a solvent (which may be N-methylpyrrolidone, without particular limitation) to obtain a solution B; 3) adding solution B to solution A and continuing to disperse the solution until uniform, to obtain a solution C; 4) adding a thixotropic agent to solution C, and dispersing the solution uniformly to obtain an insulating coating slurry.
[0022] A second aspect of the present application provides a battery electrode sheet, comprising the insulating coating slurry provided in the first aspect.
[0023] Specifically, the battery electrode sheet includes a current collector and a coating area located on at least one surface of the current collector, the coating area including an active material coating area, a mutual dissolution coating area and an insulating coating area; the active material coating area is located in the central area of the current collector, and the area of the active material coating area is designed according to the battery capacity requirements; the insulating coating area is located at the edge of the active material coating area, and the insulating coating slurry described in the first aspect of the present application is coated in the insulating coating area, and the width of the insulating coating area is adjusted and formulated according to the coating equipment capacity / cost and the requirements of the back-end equipment (CCD identification equipment), for example, it can be 4-10mm; the mutual dissolution coating area is located between the active material coating area and the insulating coating area, and is formed by mutual dissolution and interpenetration after the active material coating and the insulating coating come into contact.
[0024] One of the purposes of the present application is to reduce the mutual dissolution and interpenetration phenomenon after the active material coating and the insulating coating come into contact, that is, to reduce the width of the mutual dissolution coating zone, for example, to control the width of the mutual dissolution coating zone to ≤200μm, the smaller the width, the better, and the ideal state is that the width of the mutual dissolution coating zone is close to zero, that is, there is no mutual dissolution and interpenetration phenomenon after the active material coating and the insulating coating come into contact. The present application controls the width of the mutual dissolution coating zone by controlling the thixotropy of the insulating coating slurry. The greater the thixotropy of the insulating coating slurry within a certain range, the faster its viscosity increases after leaving the coating die, the less likely it is to have mutual dissolution and interpenetration with the active material slurry, and the smaller the width of the mutual dissolution coating zone.
[0025] The battery electrode sheet can be a positive electrode sheet or a negative electrode sheet. Correspondingly, the active material coating area is coated with positive active material or negative active material, and both use positive active material slurry or negative active material slurry available in the art without special limitation.
[0026] The preparation method of the battery electrode sheet comprises the following steps: applying the active material slurry to the middle area of at least one surface of the current collector, applying the insulating coating slurry to the edge of the active material slurry; and after drying, forming the active material coating area and the insulating coating area respectively. During the coating and drying process, part of the insulating coating slurry and the active material slurry come into contact and dissolve and interpenetrate each other, so that a mutually soluble coating area is formed between the active material coating area and the insulating coating area.
[0027] The coating pump pressure used in the preparation method of the battery electrode sheet is ≤1kPa. The present application improves the viscosity of the insulating coating slurry after coating by improving the thixotropy of the insulating coating slurry, thereby avoiding the increase in pump pressure caused by simply increasing the slurry viscosity, which is conducive to industrial production.
[0028] A third aspect of the present application provides a battery, comprising the insulating coating slurry of the first aspect, and / or the battery electrode sheet of the second aspect.
[0029] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0030] 1) The present application adds a thixotropic agent to the insulating coating slurry, and uses it in combination with an insulating filler and a binder to form a three-dimensional network structure in the slurry system, thereby improving the thixotropic index of the insulating coating slurry, increasing the thixotropy of the insulating coating slurry, and improving the viscosity of the insulating coating slurry under low shear without increasing the coating pump pressure (to ensure processability).
[0031] 2) The battery electrode sheet of the present application uses the above-mentioned insulating coating slurry with a large thixotropic index. During the high-speed coating process, the mutual dissolution and interpenetration between the active material coating area and the insulating coating area can be minimized. The width of the obtained mutual dissolution coating area is ≤200μm, which improves the accuracy of CCD recognition, reduces the loss of active materials, and is beneficial to improving the energy density of lithium batteries and improving safety performance.
[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 . The photo of the positive electrode of Example 3 under a 400x microscope shows that the width of the mutual dissolution coating area is 32.81μm;
[0034] Figure 2 . The photo of the positive electrode of Example 8 under a 400x microscope shows that the width of the mutual dissolution coating area is 27.63μm;
[0035] Figure 3 From the 400x microscope photo of the positive electrode of Comparative Example 3, it can be seen that the width of the mutual dissolution coating zone is 645.92 μm. DETAILED DESCRIPTION
[0036] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0038] In the description of the embodiments of the present application, “plurality” means more than two, unless otherwise clearly and specifically defined.
[0039] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0040] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0041] In the following specific embodiments, the substances used are all commercially available chemicals, among which boehmite (BG613) was purchased from Yishitong; alumina (SAO-030) was purchased from Sinoceramic Materials; polyvinylidene fluoride PVDF (HSV 900, Mw is 900000) was purchased from Arkema; polymethyl methacrylate PMMA (Mw is 35000) was purchased from Maclean; polyacrylic acid PAA (Mw is 450000) was purchased from Aladdin; polyamide wax (Ceridust3910) was purchased from Clariant; hydroxyethyl cellulose was purchased from Maclean; polyisoprene (POLYISOPRENE 2200) was purchased from Sinopec; fumed silica (HB-202N) was purchased from Huifu Nano; polyurea thixotropic agent (Anjeka 4410) was purchased from Anjikang; and organic bentonite thixotropic agent (HFGEL-40D) was purchased from Zhejiang Fenghong New Materials Co., Ltd.
[0042] Example 1
[0043]
Positive electrode insulation coating slurry
[0044] A positive electrode insulating coating slurry comprises the following components:
[0045] Insulating filler 80 parts by mass,
[0046] 20 parts by mass of polymer binder,
[0047] Thixotropic agent 5 parts by mass;
[0048] The invention discloses a method for preparing an insulating coating slurry, comprising: 1) dispersing an insulating filler in N-methylpyrrolidone to obtain a solution A; 2) dispersing a polymer binder in N-methylpyrrolidone to obtain a solution B; 3) adding the solution B to the solution A and continuing to disperse the solution until uniform to obtain a solution C; and 4) adding a thixotropic agent to the solution C and dispersing the solution uniformly to obtain the insulating coating slurry.
[0049] The viscosity of the insulating coating slurry was tested at a shear rate of 1 / s and 50 / s at room temperature, and the thixotropic index was calculated. The results are recorded in Table 1.
[0050]
Cathode active slurry
[0051] The positive electrode active slurry includes the following components:
[0052] Positive electrode active material (lithium iron phosphate LFP) 95 parts by mass,
[0053] Second binder (PVDF) 2.5 parts by mass,
[0054] The second conductive agent (conductive carbon black SP) 2.5 parts by mass;
[0055] The method for preparing positive electrode active slurry comprises: 1) dispersing a second binder in N-methylpyrrolidone to obtain a solution H; 2) adding a second conductive agent to the solution H and dispersing it uniformly to obtain a conductive binder; adding a positive electrode active material to the conductive binder and dispersing it uniformly to obtain a positive electrode active slurry.
[0056]
Positive electrode
[0057] A positive electrode sheet, the preparation method of which is as follows: coating the positive electrode active slurry on the middle area of one side surface of the current collector aluminum foil; coating the positive electrode insulating coating slurry on the edge of the positive electrode active material slurry; after drying, forming the active material coating area and the insulating coating area respectively. During the coating and drying process, part of the insulating coating slurry and the active material slurry are mutually dissolved and interpenetrated after contact, and a mutually soluble coating area is formed between the active material coating area and the insulating coating area. After the positive electrode sheet is dried, the width of the mutually soluble coating area is measured to be 42μm. During the coating process, the coating equipment monitors the coating pump pressure in real time, and the pump pressure is about 500Pa.
[0058] Examples 2-10 and Comparative Examples 1-3
[0059] The insulating coating slurry was prepared using the substances and compositions in Table 1, and the other contents were the same as those in Example 1.
[0060] Embodiment 11
[0061]
Negative electrode insulation coating slurry
[0062] A negative electrode insulating coating slurry comprises the following components:
[0063] Insulating filler 80 parts by mass,
[0064] 20 parts by mass of polymer binder,
[0065] Thixotropic agent 5 parts by mass;
[0066] The preparation method of the insulating coating slurry is the same as that of Example 1.
[0067]
Negative electrode active slurry
[0068] The negative electrode active slurry includes the following components:
[0069]
[0070] The preparation method of negative electrode active slurry comprises: 1) mixing the negative electrode active material and the third conductive agent evenly; 2) adding a thickener and an appropriate amount of deionized water to the powder in step 1) in batches and dispersing them evenly; 3) adding a third binder and an appropriate amount of deionized water and dispersing them evenly; 4) adding an appropriate amount of deionized water to adjust the slurry viscosity to about 3000cp to obtain the desired negative electrode active slurry.
[0071]
Negative electrode
[0072] A negative electrode sheet, the preparation method of which is as follows: coating the negative electrode active slurry on the middle area of one side surface of the current collector copper foil; coating the negative electrode insulating coating slurry on the edge of the negative electrode active material slurry; after drying, forming an active material coating area and an insulating coating area respectively. During the coating and drying process, part of the insulating coating slurry and the active material slurry are mutually dissolved and interpenetrated after contact, and a mutually soluble coating area is formed between the active material coating area and the insulating coating area. After the negative electrode sheet is dried, the width of the mutually soluble coating area is measured to be 76μm. During the coating process, the coating equipment monitors the coating pump pressure in real time, and the pump pressure is about 600Pa.
[0073] Table 1 Materials, compositions and performance parameters of insulating coating slurries of Examples 1-11 and Comparative Examples 1-3
[0074]
[0075]
[0076] The thixotropic index TI in Table 1 is calculated by the following formula:
[0077]
[0078] Among them, η 1 / s is the viscosity of the insulating coating slurry at a shear rate of 1 / s at room temperature;
[0079] η 50 / s It is the viscosity of the insulating coating slurry at a shear rate of 50 / s at room temperature;
[0080] The above η 1 / s and η 50 / sAll of them are obtained by testing the flow curve of the slurry using a HAAKE MARS40 rheometer and a 02180952.P35 / Ti mold.
[0081] Herein, "normal temperature" may specifically refer to any temperature between 20°C and 30°C, such as 20°C, 22°C, 25°C, 28°C or 30°C, etc., with 25°C being more common.
[0082] Table 2 Parameters of positive electrode sheets of Examples 1-11 and Comparative Examples 1-3
[0083]
[0084] It can be seen from the data in Table 1 and Table 2 that the mass ratio of the insulating filler, the binder and the thixotropic agent has a great influence on the performance of the insulating coating slurry. The mass ratio of the three in Examples 1-6 is within an appropriate range. A complete three-dimensional network structure can be formed in the insulating coating slurry system. Under the action of low shear force after coating, the slurry viscosity increases rapidly, the mutual dissolution of the active material coating and the insulating coating is not obvious, and the width of the mutual dissolution coating area is small, which effectively solves the technical problem of mutual penetration of the slurry in the active material coating area and the insulating coating area on the electrode current collector at a higher coating rate, and the coating pump pressure is less than 1 kPa, which can meet the needs of actual production.
[0085] It can be seen from Examples 1-8 and Comparative Example 1 that when the ratio of thixotropic agent to insulating filler and binder is too low, the thixotropic index is small, and a perfect three-dimensional network structure cannot be formed in the insulating coating slurry system. Under the action of low shear force after coating, the slurry viscosity cannot be rapidly increased, and the active material coating and the insulating coating are easily miscible, resulting in an excessively large width of the miscible coating area. When no thixotropic agent is used, such as in Comparative Example 3, the width of the miscible coating area is further increased.
[0086] It can be seen from Examples 1-8 and Comparative Example 2 that when the proportion of thixotropic agent to insulating filler and binder is too large, the thixotropic index TI increases accordingly, and the viscosity of the insulating coating under low shear is relatively large. Although the problem of mutual solubility can be solved, it causes the coating pump pressure to be too high, resulting in failure of coating.
[0087] It can be seen from Examples 6, 9 and 10 that when the specific surface area of fumed silica is large or small, the thixotropic index is too large or too small, which is not conducive to the slurry utilizing thixotropy to play a role.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. An insulating coating slurry, characterized in that: It comprises an insulating filler, a binder and a thixotropic agent; the mass ratio of the insulating filler to the binder is (90:10)-(60:40); the mass of the thixotropic agent is 0.1%-20% of the sum of the mass of the insulating filler and the binder.
2. The insulating coating slurry according to claim 1, characterized in that: The mass ratio of the insulating filler to the adhesive is (85:15)-(70:30).
3. The insulating coating slurry according to claim 1 or 2, characterized in that: The mass of the thixotropic agent is 1%-10% of the sum of the mass of the insulating filler and the adhesive.
4. The insulating coating slurry according to any one of claims 1 to 3, characterized in that: The insulating coating slurry has a viscosity of 1000-10000 mPa·s at room temperature and a shear rate of 50 / s; Preferably, the thixotropic index of the insulating coating slurry is 15≤TI≤50.
5. The insulating coating slurry according to any one of claims 1 to 4, characterized in that: The insulating coating slurry has a viscosity of 1500-4000 mPa·s at room temperature and a shear rate of 50 / s; Preferably, the thixotropic index of the insulating coating slurry is 20≤TI≤40.
6. The insulating coating slurry according to any one of claims 1 to 5, characterized in that: The insulating filler includes at least one of aluminum oxide, boehmite, magnesium oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, yttrium silicon oxide, barium zirconate, aluminum nitride, silicon nitride, and barium titanate.
7. The insulating coating slurry according to any one of claims 1 to 6, characterized in that: The polymer binder comprises at least one of polyvinylidene fluoride and its modified products, polyacrylic acid polymers, polyvinyl acetate polymers, polyacrylonitrile polymers, polyacrylate polymers, polyurethane polymers, polyurea polymers, and polyimide polymers.
8. The insulating coating slurry according to any one of claims 1 to 7, characterized in that: The thixotropic agent comprises an inorganic thixotropic agent and / or an organic thixotropic agent; Preferably, the inorganic thixotropic agent includes at least one of fumed silica, precipitated silica, organic bentonite, metal soap, asbestos, kaolin, and attapulgite; Preferably, the specific surface area of the fumed silica and / or precipitated silica is 50-500 m 2 / g; more preferably 100-280m 2 / g; more preferably 130-170m 2 / g; Preferably, the organic thixotropic agent includes at least one of polyurea, polyethylene wax, polyamide wax, polyisoprene, hydroxyethyl cellulose, hydrogenated castor oil, and polyvinyl chloride.
9. A battery electrode sheet, characterized in that: The insulating coating slurry comprises the insulating coating slurry according to any one of claims 1 to 8.
10. A battery, characterized in that: It comprises the insulating coating slurry according to any one of claims 1 to 8, and / or the battery electrode sheet according to claim 9.
Citation Information
Cited By
Carbon-coated current collector and preparation method and application thereof
CN121617973A